2007
DOI: 10.1300/j465v27n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Feasibility and Efficacy of a Brief Motivational Intervention with Psychophysiological Feedback for Cocaine Abuse

Abstract: Motivational interviewing (MI) with personalized feedback, particularly related to biological markers of risk or harm, has been found effective for alcohol use disorders, but has not been fully investigated in cocaine use disorders. A randomized, controlled pilot study evaluating the feasibility and preliminary efficacy of a brief MI intervention using EEG/ERP graphical feedback for cocaine abusers was conducted. Treatment-seeking cocaine abusers (N = 31) were randomly assigned to a two-session MI intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Several studies of brief MI with cocaine abusers (Stotts et al, 2001, 2006), including our own pilot study (Sokhadze et al, 2005), reported that cocaine dependent patients with lower initial motivation to change following brief MI intervention were more likely to achieve abstinence than those who did not receive MI intervention. Due to its brevity, MI is best suited to enhance compliance and facilitate treatment engagement (Burke et al, 2003; Miller & Rollnick, 2002; Treasure, 2004), which was one of the main rationales why we selected MI to engage patients in neurofeedback-based biobehavioral neurotherapy.…”
Section: Introductionmentioning
confidence: 82%
“…Several studies of brief MI with cocaine abusers (Stotts et al, 2001, 2006), including our own pilot study (Sokhadze et al, 2005), reported that cocaine dependent patients with lower initial motivation to change following brief MI intervention were more likely to achieve abstinence than those who did not receive MI intervention. Due to its brevity, MI is best suited to enhance compliance and facilitate treatment engagement (Burke et al, 2003; Miller & Rollnick, 2002; Treasure, 2004), which was one of the main rationales why we selected MI to engage patients in neurofeedback-based biobehavioral neurotherapy.…”
Section: Introductionmentioning
confidence: 82%
“…The goal of these training studies was to enhance attention during cognitive involvement rather than induce a relaxed state as in the previous study with alcoholics. One study employed a between-subjects design to investigate the effect of adding two sessions of neurofeedback to treatment as usual (Stotts et al, 2006). Feedback was provided from the P300 signal, as an index of cognitive involvement, while participants were attending to visual stimuli.…”
Section: Cognitive Interventionsmentioning
confidence: 99%
“…Angela Stotts and colleagues (Stotts, Potts, Ingersoll, George, & Martin, 2006) at the University of Texas at Houston, in collaboration with researchers at Rice University, used motivational interviewing (MI) with personalized feedback, particularly employing the ERP markers of deficiencies in selective attention task produced by cocaine abuse in crack addicts. In a randomized, controlled pilot study these authors (Sokhadze, Martin, Stotts, & Potts, 2004;Sokhadze, Potts, Martin, & Stotts, 2005;Stotts et al, 2006) evaluated the feasibility and preliminary efficacy of a brief MI intervention using EEG=ERP graphical feedback for crack cocaine abusers. Treatment-seeking cocaine abusers (N ¼ 31) were randomly assigned to a two-session MI intervention or a general educational drug counseling (control) condition.…”
Section: Integration Of Cognitive Neuroscience Approaches In Assessmementioning
confidence: 99%